Analysis of The Application of STEAM-Based Learning - Harjanty, Rokyal; Hardianti, Farlina (Indonesian Journal of Early Childhood Education Studies, 2020)
This study aims to see how the application of STEAM-based learning in the learning process. Knowing the description of the process of implementing STEAM-based learning. This research method uses descriptive research in the form of a survey method. This research uses data collection techniques through non-test techniques conducted at RA Perwanida Praya. The results of the study were analyzed through the Editing, Coding, and Scoring stages, which describe STEAM-based learning activities. The simple result is that the application of STEAM has appeared in the learning activities that have been applied but the teacher still does not fully understand STEAM learning related to its elements and aspects.